2016
DOI: 10.1590/s1679-45082016ao3372
|View full text |Cite
|
Sign up to set email alerts
|

Use of cuff tear arthroplasty head prosthesis for rotator cuff arthropathy treatment in elderly patients with comorbidities

Abstract: Objective To evaluate the clinical and functional behavior of patients undergoing cuff tear arthroplasty at different stages of the disease.Methods Cuff tear arthroplasty hemiarthroplasties were performed in 34 patients with rotator cuff arthropathy and associated comorbidities, classified according to Seebauer. The mean age was 76.3 years, and the sample comprised 23 females (67.6%) and 11 males (32.4%). The mean follow-up period was 21.7 months, and evaluations were performed using the Visual Analog Scale fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…The 3 patients who were unsatisfied experienced superior escape of the hemiarthroplasty. When comparing the primary use of CTA designs in patients with severe arthropathy (Seebauer type IIB disease), Carvalho et al 12 reported statistically significant improvements in pain, range of motion, and functional scores with no difference between Seebauer classification groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3 patients who were unsatisfied experienced superior escape of the hemiarthroplasty. When comparing the primary use of CTA designs in patients with severe arthropathy (Seebauer type IIB disease), Carvalho et al 12 reported statistically significant improvements in pain, range of motion, and functional scores with no difference between Seebauer classification groups.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally indicated in low-demand, elderly patients with CTA and a primary complaint of pain, the CTA design reliably reduces pain while providing modest function within the daily activities of this population. 3 , 8 , 12 , 18 , 19 , 29 , 41 In addition, the benefits of a shorter operative time, lower blood loss, and low complication and reoperation rates make the CTA prosthesis a reasonable treatment option in this population. Patients should be counseled extensively regarding postoperative functional expectations, as active patients, as well as patients desiring a higher level of function, may not be satisfied postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…There was no possible to create an absolutely smooth surface with hands by the current surgical procedure. The best smooth surface can be created by arti cial prosthesis [23]. The researchers designed a GT prothesis for tuberoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Esta patología se presenta más frecuentemente en mujeres entre la sexta y séptima década de la vida, el lado dominante es el más afectado, se manifiesta por dolor crónico progresivo, crepitación y disminución del rango de movilidad. 11 La clasificación de la artropatía del manguito rotador incluye el sistema de Hamada (Tabla 3) y el sistema Seebauer. La clasificación de Hamada detalla las diferentes etapas de la lesión masiva del manguito rotador detectadas en radiografía, donde cada grado demuestra cambios en la progresión de la artropatía; mientras que la clasificación de Seebauer se refiere a una descripción biomecánica de la artropatía, donde cada estadio se distingue por el grado de migración superior del centro de rotación y de inestabilidad, dividiéndose en cuatro estadios: IA articulación estable con mínima migración debido a una contención intacta con la presencia de acetabulización del arco coracoacromial y femoralización de la cabeza humeral.…”
Section: Wwwmedigraphicorgmxunclassified